Cognitive Trend in Implementing the Third Mission of University - Nikolay D. Tskhadaya; Dmitry N. Bezgodov; Oksana I. Belyaeva (Высшее образование в России)
The concept of “cognitive trend” applied in the article summarizes the specific theoretical approaches and changes in the management practice of modern regional University. The effect of synergy in relation to University third mission, which is further specified as a valuecompetence synergy, is approved as a key goal that led to the emergence of a cognitive trend. The phenomenon of knowledge is proposed to be considered as the main motivational resource to achieve this goal, which makes it possible to associate the author’s position with a wide area of research in the modern science of education called “cognitive management”. The motivational resource of the knowledge phenomenon is substantiated in the context of the four-level model of University organizational culture. An analysis of the four-level model gives a basis to assert its exceptional relevance to the idea of the University and the objectives of its third mission. The axiological content of the University organizational culture is revealed through the reflexive analysis of the phenomena of scientific truth, scientific knowledge, and evidence as a criterion of science. The possibility of extrapolation of the value content of the University organizational culture in the regional environment is justified from the standpoint of G. Kelly’s cognitive psychology. As a source of the fundamental principles of the communicative space of the University, the authors propose the social and philosophical concepts of communication by M. M. Bakhtin, J. Habermas and K.-O. Apel.